2014
DOI: 10.1158/0008-5472.can-14-0749
|View full text |Cite
|
Sign up to set email alerts
|

PAD2 Overexpression in Transgenic Mice Promotes Spontaneous Skin Neoplasia

Abstract: Peptidylarginine deiminase 2 (PAD2/PADI2) has been implicated in various inflammatory diseases and, more recently, cancer. The goal of this study was to test the hypothesis that PAD2 promotes oncogenesis using a transgenic mouse model. We found that about 37% of transgenic mice overexpressing human FLAG-PAD2 downstream of the MMTV-LTR promoter develop spontaneous neoplastic skin lesions. Molecular and histopathologic analyses of the resulting lesions find that they contain increased levels of markers for invas… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 53 publications
0
39
0
Order By: Relevance
“…In contrast to colorectal cancer, an oncogenic role for PADI2 has been reported in breast cancer and squamous carcinomas (15,16). In a cell culture model for breast cancer progression, PADI2 expression correlated with the transformed phenotype and cells and xenografted tumors were sensitive to Cl-amidine treatment (15).…”
Section: Padi2 Has An Ambivalent Role In Cancermentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast to colorectal cancer, an oncogenic role for PADI2 has been reported in breast cancer and squamous carcinomas (15,16). In a cell culture model for breast cancer progression, PADI2 expression correlated with the transformed phenotype and cells and xenografted tumors were sensitive to Cl-amidine treatment (15).…”
Section: Padi2 Has An Ambivalent Role In Cancermentioning
confidence: 99%
“…In a cell culture model for breast cancer progression, PADI2 expression correlated with the transformed phenotype and cells and xenografted tumors were sensitive to Cl-amidine treatment (15). Mice overexpressing PADI2 in a panel of tissues including skin and mammary epithelia spontaneously developed squamous cell carcinomas in the skin in 37% of the cases but no other tumors (16). In vitro data suggested that overexpression of PADI2 in skin carcinoma cells could favor epithelial-to-mesenchymal transitions and thus increase the cells' migratory capacity (16).…”
Section: Padi2 Has An Ambivalent Role In Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…Dr. Coonrod's lab has shown that PAD2 expression is up-regulated in tamoxifen-resistant breast cancer cells [10]. While they predicted that PAD2 might be a driver of breast cancer, unexpectedly, overexpression of PAD2 in mice by the murine mammary tumor virus promoter led to dysplastic tumors in skin cells, but not in mammary glands [11]. This work suggested that PAD2-driven oncogenesis in the skin was due to increased production of inflammatory cytokines, which were not observed in the mammary epithelium.…”
Section: Introductionmentioning
confidence: 99%